COMPARATIVE STUDY OF CARBETOCIN VS OXYTOCIN IN PREVENTION OF PPH FOLLOWING VAGINAL DELIVERY - Dr. Revathi Mallikarjuna Y; Dr. Mamatha (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Postpartum haemorrhage [PPH] is the most common cause of maternal death. Oxytocin is the standard therapy for the prevention of postpartum haemorrhage, but it requires cold storage, which is not available in many parts of country. In this study an attempt is made to compare carbetocin [heat stable oxytocin] to the traditional oxytocin in the prevention of postpartum haemorrhage. More such studies may be helpful just to include carbetocin as an additional drug to prevent PPH in rural areas where there is no cold chain.Aim: To study use of heat stable carbetocin in prevention of PPH. To prove heat stable carbetocin is equally effective or no inferior to oxytocin in preventing PPH.Methods: A prospective study carried out from August 2022 - January 2024. The main source of data was collected from the 58 cases and 58 controls attending Ramaiah Medical College and Hospital for delivery, a tertiary care centre in Karnataka, admitted under OBG department of Ramaiah Hospital, Bengaluru . A complete data is collected by history taking, and general, systemic and obstetrics examination. Further haemoglobin of the patient before and after delivery is assessed for effectiveness of carbetocin comparable to oxytocin in preventing PPH. Data was entered into an excel spreadsheet, and descriptive statistics such as mean, standard deviation, frequency, and percentage was computed. The statistical analysis was carried out using “SPSS (Statistical Package for Social Sciences) version 22 (IBM SPASS statistics [IBM corp. released 2011])”.CONCLUSIONS: our study shows that a single dose of intravenous carbetocin 100 mcg may be equally effective as compared to a single intramuscular dose of oxytocin 10 IU in reducing postpartum blood loss with a smaller drop in haemoglobin levels and low incidence of adverse effects. Carbetocin has the potential to be considered as a good alternative to conventional uterotonic agents used in managing the third stage of labour following vaginal and caesarean delivery and prevention of postpartum haemorrhage.